Impacto das políticas de fomento à inovação no Brasil sobre o gasto em atividades inovativas e em atividades de P&D das empresas - Avellar, Ana Paula (Estudos Econômicos (São Paulo), 2009)
Technology policies have been part of economical agenda in the developed countries as well as in the periphery. The generalized use of these incentives has culminated in a large international discussion questioning its effective capacity to stimulate (or not) the benefited companies. This work intends to develop an evaluating empirical exercise of three Brazilian programs of tax incentives and financial incentives to technological activities: Industrial Technological Developing Program (PDTI), National Fund for Scientific and Technological Development (FNDCT) and the Support Program for Technological Development of National Companies (ADTEN). In order to capture the effects of these programs on the behavior of benefited companies in relation to those which were not benefited, concerning the decision of expenses in technological activities and to innovative effort, an econometric method will be applied the Propensity Score Matching. The conclusion of this research is that the Brazilian programs stimulated the benefited companies.